Implementasi Model Pembelajaran Sentra Seni dalam Mengembangkan Kreativitas Anak di TK IT Nurul Ilmi Tahun Ajaran 2023/2024 - Zahra, Silvia; Pakpahan, Rustam; Sitorus, Ahmad Syukri (Lembaga Yasin AlSys, 2024)
This research aims to describe children's creativity at the IT Nurul Ilmi Kindergarten, to determine the process of implementing the arts center learning model in developing children's creativity at the IT Nurul Ilmi Kindergarten, and to identify obstacles to the implementation of the arts center learning model in developing children's creativity at the IT Nurul Ilmi Kindergarten. . This research methodology uses a qualitative approach. This approach is carried out holistically, by explaining phenomena through words and language. The subjects in this research were the principal, center teacher, class teacher and students at the arts center at TK IT Nurul Ilmi. The researcher's data collection process used observation, interviews and documentation. The results of the research reveal that 1) children's creativity in the arts center has developed quite well in terms of the creativity process and forms of creativity, 2) the process of implementing the arts center learning model in developing children's creativity at the IT Nurul Ilmi Kindergarten is in accordance with the procedures in the learning center, namely by implementing center learning steps, 3) obstacles to implementing the arts center learning model in developing children's creativity at the IT Nurul Ilmi Kindergarten, namely obstacles in planning and implementation, obstacles in eval_uation and assessment, obstacles in making crafts and time constraints.